2017
DOI: 10.1002/2016gc006568
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diatom microfossils on sediment shear strength and slope stability

Abstract: Diatom microfossils have been detected in many natural marine sediment deposits around the globe and are held responsible for the disobedience to well-established geotechnical relationships between index-properties and shear strength. We revisit the static shear strength and present the first cyclic undrained shear strength experiments on diatom microfossil-clayey-silt mixtures to study the role of diatoms on submarine slope stability. It is attested that the angle of internal friction (U) increases with diato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 53 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…Given its morphology of hollow structure, the diatomite has a high porosity which helps it to retain a high amount of water. Other characteristics found in the literature are that they present a rough and abrasive surface, low density, large surface area, and absorbent capacity [12,13]. These singular characteristics govern the behavior of some soil deposits, leading to an increment in the void ratio and Atterberg limits but also increasing the friction angle, controverting the fundamentals established in the classic mechanical of soils.…”
Section: Introductionmentioning
confidence: 99%
“…Given its morphology of hollow structure, the diatomite has a high porosity which helps it to retain a high amount of water. Other characteristics found in the literature are that they present a rough and abrasive surface, low density, large surface area, and absorbent capacity [12,13]. These singular characteristics govern the behavior of some soil deposits, leading to an increment in the void ratio and Atterberg limits but also increasing the friction angle, controverting the fundamentals established in the classic mechanical of soils.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to a higher diatom content in the background sediments of lake Calafquén, illustrated by a combination of lower magnetic susceptibility and abundant bright green laminations identified as diatom blooms (Moernaut et al., 2014 ; Van Daele et al., 2015 ). Through high particle interlocking and surface roughness, sediments’ shear strength increases with diatom content (Wiemer & Kopf, 2017 ) resulting in lower erodibility and lower susceptibility to shear‐induced deformation.…”
Section: Discussionmentioning
confidence: 99%
“…The exception is that some intervals at Site 887 also contain siliceous diatom‐rich layers [ Rea et al ., ]. Recent experimental work by Wiemer and Kopf [] has shown that the presence of diatoms in sediment can result in higher shear strength relative to siliciclastic sediments. For this reason we exclude all diatom‐rich units from our analysis.…”
Section: Methodsmentioning
confidence: 99%